Do entrepreneur-focused facility incentives create economic impacts? Evidence from Indiana. Issue 3 (11th July 2018) - Hicks, Michael; Faulk, Dagney G.
Abstract : Purpose: As a component of a benefit-cost analysis into the efficacy of publicly funded facility incentives, the purpose of this paper is to examine the county-wide impact of business incubators, makerspaces and co-working spaces on employment, proprietor's employment and the average wage per job. The period under analysis is 1971 through 2015 across Indiana's 92 counties. Design/methodology/approach: Using a unique data set on facility incentives in Indiana, a spatial panel model, which includes a unique identification strategy to account for underlying conditions identified as a source of incubator success in earlier studies, is developed. Findings: This study finds no statistically significant impact of these facilities on total employment or average wage per job during this period. There is a statistically meaningful impact of co-working spaces on proprietor's employment, but the effect is an economically insignificant one-time increase of 2.3 jobs in the typical county, which can be interpreted as shifting employment from traditional employment to proprietorship employment. Originality/value: This is the first empirical estimate of the contribution of modern facility incentives on measures of local economic activity.